2021
DOI: 10.1038/s41598-021-86171-9
|View full text |Cite
|
Sign up to set email alerts
|

Underlying neurological mechanisms associated with symptomatic convergence insufficiency

Abstract: Convergence insufficiency (CI) is the most common binocular vision problem, associated with blurred/double vision, headaches, and sore eyes that are exacerbated when doing prolonged near work, such as reading. The Convergence Insufficiency Neuro-mechanism Adult Population Study (NCT03593031) investigates the mechanistic neural differences between 50 binocularly normal controls (BNC) and 50 symptomatic CI participants by examining the fast and slow fusional disparity vergence systems. The fast fusional system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Regarding double vision among digital device users, data on the risk factors are lacking, even though double vision may indicate a more severe problem (convergence insufficiency) ( Alvarez et al, 2021 ) aggravated during intense close work ( Barnhardt et al, 2012 ). Studies have demonstrated a significant association between double vision and both short term (less than 4 h a day ( Nunes et al, 2018 )) and long term (more than 6 h a day ( Comério et al, 2017 )) use of the computer.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding double vision among digital device users, data on the risk factors are lacking, even though double vision may indicate a more severe problem (convergence insufficiency) ( Alvarez et al, 2021 ) aggravated during intense close work ( Barnhardt et al, 2012 ). Studies have demonstrated a significant association between double vision and both short term (less than 4 h a day ( Nunes et al, 2018 )) and long term (more than 6 h a day ( Comério et al, 2017 )) use of the computer.…”
Section: Discussionmentioning
confidence: 99%
“…In young adults, base-in prism reading glasses can reduce symptoms associated with exophoria, but do not seem to change near point of convergence or fusional vergence 53 . The high heterogeneity among previous trials in terms of intervention techniques, treatment protocols, and tools used to evaluate binocular vision, warrants further research in the topic 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, common conservative interventions include the use of prism-lensed glasses, alone or combined with oculomotor training. However, evidence about their effectiveness is scant and unclear 12 , and even the most effective approaches are only successful in some cases and require long treatment hours 13 , which may decrease adherence. Thus, there is a need for novel therapeutic protocols and new research on this topic is warranted 12,13 .…”
mentioning
confidence: 99%
“…For females, their hormonal changes may alter the eye's homeostasis, which may cause blurred vision (Gong et al, 2015). Regarding double vision among digital device users, data on the risk factors are lacking, even though double vision may indicate a more severe problem (convergence insufficiency) (Alvarez et al, 2021) aggravated during intense close work (Barnhardt et al, 2012). Studies have demonstrated a significant association between double vision and both short term [less than 4 hrs a day (Nunes et al, 2018)] and long term [more than 6 hrs a day (Comério et al, 2017)] use of the computer.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%